The cost of energy efficiency programs: Estimates from utility-reported datasets. (15th January 2022) - Knight, Patrick; Biewald, Bruce; Takahashi, Kenji
Abstract: Electric utilities and state regulators increasingly rely on energy efficiency to meet energy needs. However, in many jurisdictions, the cost-effectiveness of energy efficiency is still debated. Previous estimates of the cost of saved energy have relied on studies of limited program portfolios, or analysis of datasets that are proprietary, not easily verified, or outdated. Based on analysis of costs and savings self-reported by over 700 electric utilities in their Form 861 document filings, released annually from 2010 to 2019 by the U.S. Energy Information Administration (EIA), we estimate a utility cost of energy efficiency of $0.024 per kWh. This value suggests that energy efficiency programs are typically cost-effective relative to supply-side energy resources. Furthermore, as this value is in line with other estimates of the cost of saved energy from American Council for an Energy-Efficient Economy and Lawrence Berkley National Laboratory, among other sources, it suggests that EIA's Form 861 is a reasonably reliable data source for energy efficiency costs and savings, despite being populated with self-reported data. Finally, our analysis suggests a compelling relationship between the cost of saved energy and the size of program spending, providing evidence to policymakers of how these costs might change for future programs. Highlights: ∙Utility-reported data is reasonably reliable for deriving costs of saved energy. ∙Historical data analysis suggests a utility cost of energy efficiency of $0.024/kWh. ∙Utility costs of saved energy are low, but increase with increases in program size.